2022
DOI: 10.2169/internalmedicine.9223-21
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity against the BNT162b2 mRNA COVID-19 Vaccine in Rheumatic Disease Patients Receiving Immunosuppressive Therapy

Abstract: Objective To investigate the serum total antibody (immunoglobulin M and immunoglobulin G) titre against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike protein receptor-binding domain following BNT162b2 messenger ribonucleic acid (mRNA) coronavirus disease 2019 (COVID-19) vaccination in Japanese rheumatic disease patients undergoing immunosuppressive therapy. Methods The serum antibody titre against SARS-CoV-2 spike protein was analysed in 123 outpati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 20 publications
0
12
0
1
Order By: Relevance
“…Indeed, other large studies investigating antibody responses to COVID‐19 vaccines in HSCT recipients found that immunosuppressive therapy significantly decreased serological response to vaccine in HSCT recipients 15,18,29 . Furthermore, no patients in our cohort received mycophenolate mofetil or Janus kinase inhibitors, both of which have been shown to significantly reduce serological response to COVID‐19 vaccine 30,31 …”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Indeed, other large studies investigating antibody responses to COVID‐19 vaccines in HSCT recipients found that immunosuppressive therapy significantly decreased serological response to vaccine in HSCT recipients 15,18,29 . Furthermore, no patients in our cohort received mycophenolate mofetil or Janus kinase inhibitors, both of which have been shown to significantly reduce serological response to COVID‐19 vaccine 30,31 …”
Section: Discussionmentioning
confidence: 81%
“… 15 , 18 , 29 Furthermore, no patients in our cohort received mycophenolate mofetil or Janus kinase inhibitors, both of which have been shown to significantly reduce serological response to COVID‐19 vaccine. 30 , 31 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…K. Sugihara ИВРЗ (123) Pfizer МТ (35), ГИБП (29), Значимое снижение титров АТ и соавт. [36] Контроль ( 43) ГК (50) и др. у больных в целом (p<0,0001) и при лечении МТ (р=0,0017) E. Simader РА (53), mРНК МТ (55), ГИБП (51), Положительный АТ-ответ после первой и соавт.…”
Section: обзорыunclassified
“…Recently, we demonstrated and reported that immunogenicity to BNT162b2 is decreased in Japanese patients with RMDs under methotrexate treatment, similar to Western reports. [ 18 ] However, the differential effects of various rheumatic disease drugs, including methotrexate, on the immunogenicity of this vaccine have not yet been fully elucidated. Therefore, we compared the immunogenicity of the BNT162b2 vaccine in Japanese patients receiving various immunosuppressive drugs for RMDs with healthy controls.…”
Section: Introductionmentioning
confidence: 99%